2023
DOI: 10.1039/d3sc02709k
|View full text |Cite|
|
Sign up to set email alerts
|

Fast and scalable solvent-free access to Lappert's heavier tetrylenes E{N(SiMe3)2}2 (E = Ge, Sn, Pb) and ECl{N(SiMe3)2} (E = Ge, Sn)

Javier A. Cabeza,
Javier F. Reynes,
Felipe García
et al.

Abstract: Iconic Lappert´s heavier tetrylenes E{N(SiMe3)2}2 (E = Ge (1), Sn (2), Pb (3)) have been efficiently prepared from GeCl2(1,4-dioxane), SnCl2 or PbCl2 and Li{N(SiMe3)2} via a completely solvent-free one-pot mechanochemical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 153 publications
0
5
0
Order By: Relevance
“…To this end, Garci ́a-Alvarez et al very recently described the preparation of Lappert's HTs mechanochemically. 72 Interestingly, not only were the reaction times shorter than those described for solution-based methods but the yields were higher in all the cases (Scheme 14).…”
Section: Synthesis Of Inorganic Compoundsmentioning
confidence: 97%
“…To this end, Garci ́a-Alvarez et al very recently described the preparation of Lappert's HTs mechanochemically. 72 Interestingly, not only were the reaction times shorter than those described for solution-based methods but the yields were higher in all the cases (Scheme 14).…”
Section: Synthesis Of Inorganic Compoundsmentioning
confidence: 97%
“…In the synthesis of the bulky Group 14 amides M{N(SiMe 3 ) 2 } 2 (M = Ge, Sn, Pb) from Li{N(SiMe 3 ) 2 } and GeCl 2 Á(1,4-dioxane), SnCl 2 , or PbCl 2 , the groups of Garcia and Garcı ´a-A ´lvarez explicitly tracked the number of equivalents of solvate molecules per metal center (to which they gave the name ''Z solv ''). 32 For the germanium reaction, Z solv = 1 by virtue of the coordinated dioxane molecule, and it was found that the yields of the Sn and Pb amides were also improved at a ratio of one equivalent of dioxane per mole of metal halide. Other than indicating that the amount of solvent was in the LAG region, the corresponding Z values for these reactions (0.21, 0.19, and 0.16 for Ge, Sn, and Pb, respectively) were less informative.…”
Section: Mechanochemistry and Additivesmentioning
confidence: 99%
“…13,14 Last year, García, García-Álvarez and co-workers reported a fast, scalable and solvent-free method to access the commonly named “Lappert's heavier tetrylenes” E[N(SiMe 3 ) 2 ] 2 (E = Ge, Sn, Pb) by a mechanochemical synthesis ( III ). 15 Earlier this year Yamashita and co-workers also reported that non-solvated dialkylaluminyl anion can be isolated from the mechanochemical reduction of the dialkylaluminium iodide with an Na/K alloy ( IV ). 16…”
mentioning
confidence: 99%